Identity on Filchneria heteroptera (Wu, 1938) (Plecoptera: Perlodidae) with a new record of Paraleuctra cercia (Okamoto, 1922) from China - Tang, Zixiang; Wang, Jie; Li, Weihai; Bozdoğan, Hakan (Zootaxa, 2024)
Filchneria heteroptera (Wu, 1938) is rediscovered from Heilongjiang Province of northeastern China. A supplementary description and illustrations including aedeagal structures based on newly collected specimens are provided. Filchneria dongruihangi Chen, 2020 is considered here as a junior synonym of F. heteroptera (Wu, 1938). Paraleuctra cercia (Okamoto, 1922) is reported from Liaoning and Heilongjiang provinces, China for the first time.